Prevalencia de retenciones placentarias y su relacion con la morbimortalidad en mujeres de 35 a 45 años de edad que fueron atendidas en el Hospital Alfredo Noboa Montenegro, Guaranda-2017 - Montenegro Chavez, Lisseth (2018)
Placental retention is one of the main puerperal complications that represent cause of maternal morbidity and mortality. The purpose of the present investigation is to establish the prevalence of placental retentions and their relationship with morbidity and mortality in women between 35 and 45 years of age. To perform this work, an observational and retrospective investigation was used. The population is made up of 1,379 women who attended the Alfredo Noboa Montenegro Hospital during 2017 and who were attended by simple eutocic births and cesarean deliveries. The sample consists of 301 women and was obtained through a statistical program Launch Stats V 2.0; The instrument for the collection of the information was the clinical histories of each patient. The data were settled and tabulated in statistical tables, for which charts and graphs were made. The results of this investigation allowed us to conclude that the prevalence rate of placental retentions is high and that its relationship with morbidity and mortality is associated with multiparity. It is recommended that the results of this research work be assessed by those who have in their hands the attention of the obstetric assistance services of the Alfredo Noboa Montenegro Hospital, in order to establish aid mechanisms that improve the care techniques specifying the attention of the work of delivery in order to reduce placental retentions and their consequences, such as postpartum hemorrhages